Resection or radiofrequency ablation of colorectal liver metastasis - Jašarović Damir; Stojanović Dragoš; Mitrović Nebojša; Stevanović Dejan (Vojnosanitetski Pregled)
Background/Aim. Liver resection is the treatment of choice for solitary colorectal liver metastases in suitable candidates. Recently, radiofrequency ablation (RFA) has become a very popular procedure in the treatment of liver metastases. The aim of this study was to compare outcomes in patients with solitary colorectal liver metastasis who had been subjected to resection or ablation. Methods. In this retrospective study we analyzed and compared patients with solitary colorectal liver metastases treated by resection or ablation in the University Hospital Centre “Dr Dragiša Mišović” in Belgrade from January 2002 until December 2009. Results. In this study 94 (67.1%) patients underwent resection whereas 46 (32.9%) patients underwent RFA. Most of the resected patients (59.6%) required major hepatectomy. The median follow-up time was 28.4 months. Tumor ablation was a significant predictor of the overall survival (p = 0.002; OR 3.75; 95% CI 1.696-8.284). Our study demonstrated longer disease free-survival in the group of resected patients compared to the RFA group (37.6 vs 22.3 months, p = 0.073). The median overall survival was 56.3 months for patients who underwent resection vs 25.1 months for those in the RFA group (p = 0.005). Conclusion. This study shows that the patients with solitary hepatic colorectal cancer metastases should be considered for hepatic resection whenever it is feasible, because this procedure provides superior long-term survival as compared to radiofrequency ablation.